Mercy Watson : something wonky this way comes something wonky this way comes - DiCamillo, Kate.; Van Dusen, Chris (Somerville, Mass. : Candlewick Press, 2009)
"Mr. and Mrs. Watson and their porcine wonder, Mercy, are off to the Bijou Drive-In"--P. [4] of cover.
"Reinforced trade ed."--P. [4] of cover.
"No. 6"--Spine.
Ages 6-8.
Keywords: Watson, Mercy (Fictitious character) -- Juvenile fiction; Swine -- Juvenile fiction; Drive-in theaters -- Juvenile fiction